2013
DOI: 10.1137/110859440
|View full text |Cite
|
Sign up to set email alerts
|

Size Bounds and Query Plans for Relational Joins

Abstract: Relational joins are at the core of relational algebra, which in turn is the core of the standard database query language SQL. As their evaluation is expensive and very often dominated by the output size, it is an important task for database query optimisers to compute estimates on the size of joins and to find good execution plans for sequences of joins. We study these problems from a theoretical perspective, both in the worst-case model, and in an average-case model where the database is chosen according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
223
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(229 citation statements)
references
References 10 publications
(11 reference statements)
3
223
0
Order By: Relevance
“…By Proposition 3.2, we can bound this number from above using the (key(A) ∪ A)-restriction of Q and D. This is a useful upper bound because any restriction of Q, as defined in Section 3, is an equi-join, and recent results [Atserias et al 2008] give tight asymptotic bounds on the size of results of equi-joins in terms of the input size. We next give an intuitive introduction to these asymptotic bounds.…”
Section: Upper Boundsmentioning
confidence: 98%
See 2 more Smart Citations
“…By Proposition 3.2, we can bound this number from above using the (key(A) ∪ A)-restriction of Q and D. This is a useful upper bound because any restriction of Q, as defined in Section 3, is an equi-join, and recent results [Atserias et al 2008] give tight asymptotic bounds on the size of results of equi-joins in terms of the input size. We next give an intuitive introduction to these asymptotic bounds.…”
Section: Upper Boundsmentioning
confidence: 98%
“…Definition 7.8 [Atserias et al 2008]. For an equi-join query Q = σ ψ (R 1 × · · · × R n ), the fractional edge cover number ρ * (Q) is the cost of an optimal solution to the linear program with variables…”
Section: Upper Boundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result has since been shown to be optimal -a classic CSP instance has polynomially many solutions in its size if and only if it has bounded fractional edge cover number [5].…”
Section: Lemma 2 ([27])mentioning
confidence: 93%
“…The "select" part of an SQL query allows users to specify a set of output variables, so that query answering amounts at enumerating all solutions rather than just deciding whether there is any. In [3], it has been shown that the enumeration problem where all variables are output variables (i.e., "SELECT *" queries where no variable is projected out) can be solved in polynomial time on a class C of queries if, and only if, the number of solutions is always polynomial, and that this is the case, if and only if, the queries in C have bounded fractional edge cover number. Similar tight worstcase bounds for conjunctive queries with arbitrary sets of output variables have been derived in [20].…”
Section: Structural Decomposition Methodsmentioning
confidence: 99%